A response token as an interactional resource for topic closing in Korean conversation - Ha, Kyoungmi (East Asian Pragmatics, 2022)
This study investigates the discourse and sequential roles of the response token kuleh-kwuna (‘I see’) in ordinary Korean conversation using the conversation analytic (CA) approach. Regarding closing sequences in English conversation, studies have shown less-abrupt ways of closing a topic by using figurative expressions, response tokens indicating shift-implicativeness and assessment (Beach, 1993; Drew & Holt, 1998; Goodwin & Goodwin,1992; Jefferson, 1984). In line with these studies on closing sequences, and furthering the previous studies of the sentence-ending suffix-kwuna, this article argues that Korean speakers often use the response token kuleh-kwuna as a resource to close a topic of conversation less abruptly. A speaker’s complete understanding of the received information and the implication of not needing further information indexed by kuleh-kwuna provide a suitable environment in which speakers can move on to the next sequence of a conversation.